(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Self-compacting concrete (SCC) is defined as concrete that can be placed normally and will flow under its own weight while maintaining its homogeneity. Full compaction and strength may therefore be achieved without the assistance of mechanical vibrations. Its development was based on the desire to improve the quality of concrete work and automate construction. It was developed in 1988.Since then, various investigations have been carried out and mainly large constructions companies have used the concrete in practical structures in Japan. Here in this report an attempt has been made to study the characteristics of self compacting concrete and the specialties in the mix design, which had given it the self-compacting capacity.